The impact of effective study strategy use in an introductory anatomy and physiology class - Firetto, Carla M.; Starrett, Emily; Montalbano, Amy Collins; Yan, Lin; Penkrot, Tonya A.; Kingsbury, Jeffrey S.; Hyatt, Jon-Philippe K. (Frontiers in Education, 2023)
Introductory courses in biology often act as a gateway for students seeking careers in healthcare and science-related fields. As such, they provide a prime entry point for innovations seeking to enhance students’ learning of foundational content. Extant innovations and interventions have been found to positively impact students’ study strategy use with concomitant impacts on course exams and grades. These innovations, however, often have associated time and other costs, which may ultimately limit more widespread use. Our study builds on prior findings by exploring the extent to which students evidence increased use of effective study strategies after engaging in a brief (i.e., 15-min), online module requiring no financial cost for students or time commitment from instructors, and whether changes in students’ use of effective study strategies are associated with changes in exam performance. The present study employed a brief, online module designed to support undergraduate students’ (n = 98) use of effective study strategies in an introductory human anatomy and physiology course. Through a pretest-posttest design, students described the strategies they used to study and completed four cognitive and metacognitive subscales before and after engaging in a brief, online module designed to teach them about effective study strategies. Results were somewhat mixed: students evidenced a modest, statistically significant increase in the number of strategies used and changes in strategy use were associated with changes in exam score only for some measures. Notably, this relationship was not moderated by GPA, suggesting that the strength of the relationship between changes in strategy use and changes in exam scores were not different depending on students’ levels of prior academic performance. Taken together, the innovation was associated with increases in students’ exam scores, irrespective of GPA, but future research should explore the refinement and extension of the innovation to explore ways that increase efficacy and impact while still balancing sustainable implementation to account for challenges associated with instructor supervision and training, financial costs, and students’ time.